Does Strategic Group Membership Affect Firm Performance? An Analysis of the German Brewing Industry - Ludwig Theuvsen; Matthias Heyder; Christoph Niederhut-Bollmann (German Journal of Agricultural Economics (GJAE), 2010)
The concept of strategic groups has been successfully applied for analyzing firm strategies, structures and performance in various industries. Based on a large-scale empirical study, this paper identifies strategic groups in the German brewing industry and analyzes the effects of group membership on economic performance. The brewing industry is an interesting research object. The severe economic crisis German breweries face in their home market and the deep structural changes reshaping the global beer industry are forcing German breweries to rethink their strategic position. The analysis reveals a limited number of strategic groups and significant performance differences between these groups. Both results are in line with the central hypotheses of the concept of strategic groups. The empirical results enable firm managers to benchmark their breweries against more successful strategic groups, to better adapt corporate and competitive strategies to firm environments, to identify more profitable strategic positions, and to take action to switch from one strategic group to another.
Keywords: 330